AlGaN-based UV-B laser diode with a wavelength of 290 nm on 1 μm periodic concavo–convex pattern AlN on a sapphire substrate. (27th April 2021) - Tanaka, Shunya; Teramura, Shohei; Shimokawa, Moe; Yamada, Kazuki; Omori, Tomoya; Iwayama, Sho; Sato, Kosuke; Miyake, Hideto; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu
Abstract: Room-temperature pulsed oscillation with a laser wavelength of 290 nm and a threshold current density of 35 kA cm −2 was achieved by fabricating a UV-B laser diode on a thick AlGaN film formed on a 1 μ m periodic concavo–convex pattern AlN (PCCP-AlN) on a sapphire substrate. The advantage of this method using PCCP-AlN is that it promotes the nucleation of AlGaN crystals. Planarization of this growth nucleus with AlGaN reduces the threading dislocation density at the top of the AlGaN growth layer while suppressing the formation of giant micrometer-sized hillocks and V-shaped pits that appear irregularly.